Selective Adoption or Comprehensive Learning? Domestic Policy Makers’ Use of International Organization and Global Management Consulting Firm Advice in Future Skills Policy Making in Canada - Linda A. White; I Younan An; Elizabeth Dhuey; Michal Perlman (International Review of Public Policy)
The fourth industrial revolution, brought about by technological innovations including artificial intelligence, automation, and advanced robotics, is already shaping many economies around the world. International Organizations (IOs) and Global Management Consulting Firms (GMCFs) are key sources of information for how domestic economies can respond to these anticipated disruptions and “future proof” their economies. But do domestic policy makers pay attention to IO and GMCF advice to inform policy making and to what extent are their ideas considered authoritative and influence domestic policy agendas? This article examines these organizations’ informational and agenda setting power in domestic policy formulation, focusing on the case of Canada’s future skills policy making community. Using qualitative research methods including thematic analysis of 26 interviews within the policy community and citation analysis of policy documents, the study reveals mixed findings. IOs and GMCFs were important sources of information, among many, for domestic policy actors in the future skills policy community. Contrary to the expectation of selective uptake of their advice based on their perceived authoritativeness, however, we find much more evidence of more comprehensive learning amongst domestic policy actors, with variation observed based on the domestic actors’ roles within their organizations.